Efforts To Increase Economic Growth By Reducing The Poverty Rate of West Sumatra Province - Subiyantoro, Heru; Zaki, Zaki (CV. Publikasi Indonesia, 2024)
The Indonesian government realizes that national development is an effort to achieve the goal of a just and prosperous society. In line with this goal, various development activities have been directed toward regional development, in relatively underdeveloped areas. Regional development is carried out in an integrated and sustainable manner according to the priorities and needs of each region with national development goals and targets that have been determined through long-term and short-term development. In reducing the number of poor people, the main thing that must be done for growth is to choose a development strategy or instrument. This means that one of the main criteria for selecting the focus sector or mainstay sector for national development is effectiveness in reducing the number of poor people. Poverty is a problem faced by all countries in the world. Poverty is considered the inability to meet a minimum standard of living. Poverty is a complex problem, so it is hoped that the government can eradicate poverty in Indonesia. One effort to improve economic performance is by carrying out national development to be able to create jobs and organize a decent life to realize the welfare of the Indonesian population. The Indonesian government realizes that national development is one of the efforts to achieve the goals of a just and prosperous society. In line with this goal, various development activities have been directed toward regional development, in fairly underdeveloped areas. Regional development is carried out in an integrated and sustainable manner according to the priorities and needs of each region with national development goals and targets that have been determined through long-term and short-term development. The type of research used is qualitative research. This research method is non-doctrinal (normative empirical) legal research, namely research that examines field theories that are developed not based on doctrine, but laws that live and develop and apply in society. The type of research in this research is also called empirical juridical research, which in other words is a type of sociological legal research and can also be called field research, namely studying applicable legal provisions and what happens in reality in society. The results of the research are that an ever-growing population demands continuous economic development. All of this requires more investment. For developing countries, rapid population growth is an obstacle to economic development, because these countries have little capital. Other researchers state that population growth and labor force growth (which occurs several years after population growth) are traditionally considered the factors that increase economic growth